Development of a Tutorial Video for Creating Digital Based Card Game Media - Faridy, Fadhil Alwa; Enawaty, Eny; Muharini, Rini (Hydrogen: Jurnal Kependidikan Kimia, 2025)
The primary objective of this study is to measure the level of validation and identify educators responses to a tutorial video on the creation of digital based card game media. This study employs a Research and Development (R&D) method, using the ADDIE model as its development framework. Data were collected through interviews, literature review, and response questionnaires. The subject of this study is a tutorial video on developing digital based card game media, which was tested with 12 chemistry teachers from six districts in Pontianak City. The selection of respondents in this study was based on the willingness of educators to participate as respondents and to provide the necessary data. The developed media were validated in terms of media and language aspects by two media experts and two languange experts, respectively. The validation results indicated that the media and language aspects achieved validity percentages of 93% and 97%, respectively. The average response percentage from chemistry educators toward the developed product was 96%. Therefore, the tutorial video for creating digital based card game media is categorized as highly valid and received very positive responses, indicating its potential for use by educators in designing digital base. The novelty of this research lies in the development of a tutorial video designed specifically to assist educators in creating digital-based card game learning media.